2013
DOI: 10.1002/pits.21682
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a One‐trial Brief Experimental Analysis to Identify Reading Fluency Interventions

Abstract: This study sought to evaluate whether a one‐trial brief experimental analysis (OTBEA) would reliably and validly identify effective treatments to improve oral reading fluency for 6 elementary school students referred for reading problems. An OTBEA was conducted with each participant to assess the effects of skill‐ and performance‐based treatment components. Following the OTBEA, an extended analysis was conducted using an alternating treatments design to experimentally assess whether predictions generated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Data matrix for immediate eect: dierence between the initial predicted values for the two conditions. Andersen et al(2013) for Terrance [their gure 1, middle right panel]. Andersen, M. N., Daly, III, A. J., & Young, N. D. (2013).…”
Section: Piecewise Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data matrix for immediate eect: dierence between the initial predicted values for the two conditions. Andersen et al(2013) for Terrance [their gure 1, middle right panel]. Andersen, M. N., Daly, III, A. J., & Young, N. D. (2013).…”
Section: Piecewise Regressionmentioning
confidence: 99%
“…Andersen et al(2013) for Terrance [their gure 1, middle right panel]. Andersen, M. N., Daly, III, A. J., & Young, N. D. (2013). Examination of a one-trial brief experimental analysis to identify reading uency interventions.…”
Section: Piecewise Regressionmentioning
confidence: 99%
“…A primary limitation to the current study was a reliance on grade‐level passages rather than employing a pretreatment experimental analysis to identify passages appropriate to each participant's instructional reading level (Andersen, Daly, & Young, ). In the present study, each of the 107 third‐grade students was assigned third‐grade‐level reading passages for progress monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…BEAs use logic from single‐case design (SCD) to test hypotheses by collecting baseline data and examining immediate changes in scores after implementing an intervention (Riley‐Tillman & Burns, 2009). For example, Andersen, Daly, and Young () compared reading fluency after an intervention with multiple instructional components to providing a reward and to a control condition with six students using one instructional session and one reading assessment for each condition. The results indicated that the instructional condition plus the reward led to the highest reading fluency for three of the students, and the reward only led to highest fluency for three other students.…”
Section: Bea Conditionsmentioning
confidence: 99%
“…There is considerable research in the applied behavior analysis and school psychology literature supporting that BEA directly links assessment to an effective intervention. BEAs have been used to identify interventions with positive effects for reading fluency (Andersen et al., ), mathematics (Carson & Eckert, ), and writing (Parker, Dickey, Burns, & McMaster, ). Most studies that examined BEA used reading fluency (Burns & Wagner, ) because it was highly linked to general reading proficiency (Fuchs, Fuchs, Hosp, & Jenkins, ), correlated well with other measures of reading (Kim, Wagner, & Foster, ; Wood, ), and is an important component of reading instruction and proficiency (Rasinski & Samuels, ).…”
Section: Bea Conditionsmentioning
confidence: 99%